É preciso falar em inglês durante as aulas de li das escolas públicas? crenças de professores em formação inicial da uft sobre o ensino de li nas escolas públicas. - Moreira, Morganna Gomes Vasconcelos (Universidade Federal do Tocantins, 2023)
The study of belief (s) about teaching-learning in English began in Brazil around the 90's. Since then several researches have been carried out within the applied linguist. Beliefs can be an unconscious phenomenon or not. Many students do not realize that their speeches about English language teaching / learning are loaded with beliefs. This monograph is guided by the concept of belief given by Barcelos, (2006) being the opinions, thoughts and ways of seeing the world and that can be constructed from the experiences of individuals. In the same way we will approach concepts, perspectives of other authors as, Almeida Filho (1993), VieiraAbrahão (2004) and Silva (2005). This work aimed to identify the beliefs of teachers in initial formation of the UFT English language course on the teaching of LI in public schools. The data were collected through a questionnaire answered by students of the federal university of Tocantins of the seventh and eighth period of English language letters, Araguaína fields. The qualitative-quantitative methodology was used to carry out this research. The data collected in this research point to three common beliefs in the UFT Letters course of the UFT on teaching English in public schools.